NUMERICAL SOLUTION OF DIFFERENTIAL EQUATIONS IN MAPLE USING THE RUNGEKUTTA METHOD - Nasriddinov Otadavlat; Isomiddinova Odilakhon (Western European Studies, 2024)
Students studying in higher education are taught in differential equations, higher mathematics and differential equations. A mathematical model of a number of processes occurring in nature is brought to the differential equation. Many of the quantities found in nature have their own law. Finding these laws directly is a much more complicated matter. Finding the connection between the quantity being considered, its rate of change and its acceleration is by nature much lighter. As a mathematical representation of this connection, however, ordinary differential equations are formed. In finding a quick and accurate solution to such equations, it is important and significant to use modern computer programs. This article addressed the issue of physics in the Maple program and obtained the result
Keywords: Mаple progrаm; fⅰrst order lⅰneаr ordⅰnаry dⅰfferentⅰаl equаtⅰon; functⅰon